HLA‐A‐B‐C‐DRB1‐DQB1 phased haplotypes in 124 Nigerian families indicate extreme HLA diversity and low linkage disequilibrium in Central‐West Africa. Issue 4 (24th August 2015) - Testi, M.; Battarra, M.; Lucarelli, G.; Isgro, A.; Morrone, A.; Akinyanju, O.; Wakama, T.; Nunes, J. M.; Andreani, M.; Sanchez‐Mazas, A.
Abstract The simultaneous typing of five‐HLA loci at high resolution and the availability of pedigree data allowed us to characterize extended five‐locus phased haplotypes in 124 Nigerian families and to compare the observed frequencies with those expected by an expectation–maximization algorithm for unphased data. Despite the occurrence of some frequent alleles at each locus (e.g. B*53:01, which is assumed to protect against Plasmodium falciparum), as many as 82% of the sampled individuals carry two unique five‐locus haplotypes and only three extended haplotypes with frequency above 1% exhibit significant linkage disequilibrium. Although preliminary, these results reveal an extreme level of HLA diversity in the Nigerian population, which reflects both its multi‐ethnic composition and the very ancient demographic history of African populations.